"But we had obtained professional / legal advice!" the disclosure conundrum and diectors' dilema - Mohd. Sulaiman, Aiman @ Nariman (Emerald Group Publishing Limited, 2013)
Purpose - In recent enforcement actions by several capital market regulators in some common law jurisdictions, the issue of directors' reliance on legal advice in relation to compliance with their statutory duties has been raised. This paper aims to discuss the dilemma faced by directors and regulators in assessing the extent to which reliance on legal advice can provide sufficient protection against allegation of breach of directors' duties and the disclosure obligation. Design/methodology/approach - This paper discusses recent case studies that highlight the often conflicting regulatory stance. Findings - These cases indicate that the disclosure conundrum is a real challenge to regulators and directors alike. These enforcement activities have resulted in mixed views as to whether these decisions have rightly upheld the standard of care expected to be exercised by directors or are unduly burdensome and not pragmatic for honest and well-meaning directors. Research limitations/ implications - The legal position is still evolving in view of the numerous regulatory actions in various jurisdictions regarding financial reporting and disclosure obligation of directors and corporations. Originality/value - Given the numerous disclosure and reporting obligations that a listed company must comply with and the regulatory enforcement actions that may be taken against the directors, it is important for directors to understand the implication of this case and similar enforcement activities on directors' oversight duty.